Sulphinpyrazone in acute myocardial infarction: studies on cardiac rhythm and renal function. Issue 6239 (23rd August 1980) - Wilcox, R G; Richardson, D; Hampton, J R; Mitchell, J R; Banks, D C
Abstract : Ninety-eight patients with acute myocardial infarction were randomly allocated to receive sulphinpyrazone 200 mg four times daily or placebo on admission to a coronary care unit. Twenty-four-hour electrocardiogram tape recordings showed no significant reduction in serious arrhythmias in the sulphinpyrazone-treated group. In addition to the expected all in serum urate concentration, patients taking sulphinpyrazone showed a persistent increase in their serum urea and creatinine concentrations when compared with those in the placebo groups (p < 0.05 and p < 0.01 respectively). These differences could not be accounted for by differences in the extent and severity of the infarction between the two groups. These results suggest that sulphinpyrazone has no discernible antiarrhythmic effect in acute myocardial infarction.